American lion : Andrew Jackson in the White House - Meacham, Jon (New York : Random House, 2008)
A thought-provoking study of Andrew Jackson chronicles the life and career of a self-made man who went on to become a military hero and seventh president of the United States, critically analyzing Jackson's seminal role during a turbulent era in history, the political crises and personal upheaval that surrounded him, and his legacy for the modern presidency
pt. 1. The love of country, fame and honor : beginnings to late 1830. -- Andy will fight his way in the world -- Follow me and I'll save you yet -- A marriage, a defeat, and a victory -- You know best, my dear -- Ladies' wars are always fierce and hot -- A busybody Presbyterian clergyman -- My white and red children -- Major Eaton has spoken of resigning -- An opinion of the President alone -- Liberty and union, now and forever -- General Jackson rules by his personal popularity -- pt. 2. I will die with the Union : late 1830 to 1834. -- I have been left to sup alone -- A mean and scurvy piece of business -- Now let him enforce it -- The fury of a chained panther -- Hurra for the hickory tree! -- A dreadful crisis of excitement and violence -- The mad project of disunion -- We are threatened to have our throats cut -- Great is the stake placed in our hands -- My mind is made up -- He appeared to feel as a father -- The people, sir, are with me -- We are in the midst of a revolution -- pt. 3. The evening of his days : 1834 to the end. -- So you want war -- A dark, lawless, and insatiable ambition! -- There is a rank due to the United States among nations -- The wretched victim of a dreadful delusion -- How would you like to be a slave? -- The strife about the next Presidency -- Not one would have ever got out alive -- I fear Emily will not recover -- The President will go out triumphantly -- The shock is great, and grief universal
Includes bibliographical references (p. [449]-462) and index
Keywords: Jackson, Andrew, -- 1767-1845; Jackson, Andrew, -- 1767-1845 -- Family; Jackson, Andrew, -- 1767-1845 -- Friends and associates; Presidents -- United States -- Biography; United States -- Politics and government -- 1829-1837